2020
DOI: 10.5152/tjar.2015.35682
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sugammadex versus Neostigmine Costs and Respiratory Complications in Patients with Obstructive Sleep Apnoea

Abstract: To compare sugammadex and neostigmine regarding the efficacy in reversing rocuronium-induced neuromuscular block, the incidence of post-operative respiratory complications and costs in patients undergoing surgery for the treatment of obstructive sleep apnoea (OSA). Methods: After obtaining ethical approval and patient consent, 74 patients in ASA physical status I or II were randomised into two groups to receive 2-mg kg −1 sugammadex (Group S) or 0.04-mg kg −1 neostigmine+0.5-mg atropine (Group N). Groups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…Patients with OSA who received sugammadex versus neostigmine had less postoperative chest radiographic changes (atelectasis, pleural effusions), 6.9% vs 16.3% (odds ratio [OR], 0.36; 95% CI, 0.18–0.8), 69 but there were no differences in postoperative mechanical ventilation or hospital length of stay. Although both studies showed a reduction in some postoperative respiratory complications, the evidence is limited because the number of patients included in the RCT (Oxford LOE: 2) was small, 68 and the observational study (Oxford LOE: 3) reported no difference in clinical outcomes. 69 …”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 97%
See 2 more Smart Citations
“…Patients with OSA who received sugammadex versus neostigmine had less postoperative chest radiographic changes (atelectasis, pleural effusions), 6.9% vs 16.3% (odds ratio [OR], 0.36; 95% CI, 0.18–0.8), 69 but there were no differences in postoperative mechanical ventilation or hospital length of stay. Although both studies showed a reduction in some postoperative respiratory complications, the evidence is limited because the number of patients included in the RCT (Oxford LOE: 2) was small, 68 and the observational study (Oxford LOE: 3) reported no difference in clinical outcomes. 69 …”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 97%
“…There are limited studies comparing the impact of different neuromuscular blocking reversal agents on postoperative respiratory complications in patients with OSA. We identified 1 RCT 68 and 1 observational study 69 that compared sugammadex to neostigmine. In the 2 studies, 209 patients with OSA and 185 patients without OSA were included.…”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that sugammadex provides faster recovery than acetylcholinesterase inhibitors, regardless of rocuronium dosage or level of neuromuscular block. Furthermore, studies have shown that sugammadex results in no residual neuromuscular blockade and faster discharge rates from the PACU when compared to acetylcholinesterase inhibitors [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, studies have focused on the effect of residual neuromuscular blockade in the immediate postoperative period and especially during patients’ stay in the PACU [9,10,11,12]. Thevathasan et al [13], however, reported on the long-term outcomes of residual neuromuscular blockade.…”
Section: Introductionmentioning
confidence: 99%